TACKLING JOINT RESEARCH SYSTEM AS THE RESPONSE TO THE GLOBALISATION ISSUE IN INDONESIAN HIGHER EDUCATION - Rahmi, Hayatur (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2022)
This report exhibits how Indonesian policymakers internationalise their Higher Education Institutions (HEIs) to answer the “global openness” in education. Joint Research (JR) has been implemented by Indonesian policymakers to do so. This research scrutinise such implemented JR by proposing an adopted European framework system in Higher Education Institutions (HEIs). This framework is the transversal dimensions of successful European countries in practising OpenEdu (dos Santos, Punie & Munoz, 2016), namely, strategy, technology, quality and leadership. As the intention of Ministry of Research, Technology and Higher Education (MoRTHE) towards JR is to increase the number of international journal publication, this research favourably recommend the implementation of JR by reforming and upgrading four categories adopted from EU OpenEdu: strategy, technology, quality and leadership. Those categories need to be adopted officially into the JR implementation to produce more international journal and be ready to compete with other institutions globally.